2020
DOI: 10.1111/anae.15267
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐centred measurement of recovery from day‐case surgery using wrist worn accelerometers: a pilot and feasibility study*

Abstract: This pilot and feasibility study evaluated wrist-worn accelerometers to measure recovery from day-case surgery in comparison with daily quality of recovery-15 scores. The protocol was designed with extensive patient and public involvement and engagement, and delivered by a research network of anaesthesia trainees. Forty-eight patients recruited through pre-operative assessment clinics wore wrist accelerometers for 7 days before (pre-operative) and immediately after elective surgery (early postoperative), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Adherence to wearables has typically been reported as the total number of days patients wore a device, rather than the consistency of wear during those days. In both postoperative and clinical trial contexts, median length of engagement has been reported at around 5 days [ 23 , 24 ]. It was notable that patients less adherent to the wearable were more likely to require escalation to physical care.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to wearables has typically been reported as the total number of days patients wore a device, rather than the consistency of wear during those days. In both postoperative and clinical trial contexts, median length of engagement has been reported at around 5 days [ 23 , 24 ]. It was notable that patients less adherent to the wearable were more likely to require escalation to physical care.…”
Section: Discussionmentioning
confidence: 99%
“…which are normally subjective and expensive, the automated systems may provide an objective, low-cost alternative, which can also be used for continuous monitoring/assessment. Some automated systems are developed to assess the behaviours of diseases such as Parkinson's disease (zia ur et al 2019;Hammerla et al 2015), autism (Ploetz et al 2012), depression (Little et al 2020); or to monitor the health status such as sleep (Zhai et al 2020;Supratak et al 2017), fatigue (Bai et al 2020;Ibrahim et al 2020), or recover-level from surgery (Ratcliffe et al 2020;Gurchiek et al 2019), etc. After collecting behaviour or physiological signals (e.g., accelerometers, ECG, audio, etc.…”
Section: Automated Behaviour Assessment Using Wearablesmentioning
confidence: 99%
“…A recent example of this approach was reported in the study by Ratcliffe et al. of recovery from surgery, where data were obtained using wrist‐worn accelerometers [12]. A PPI group was surveyed to determine the preferred type of accelerometer device, as well as the acceptability of study contacts and likely familiarity with similar technologies.…”
Section: When and How Should Patients And The Public Be Involved In R...mentioning
confidence: 99%
“…This is arguably of particular importance for clinical research in anaesthesia, critical care and perioperative medicine which all take place around the time of major life events for patients. A recent example of this approach was reported in the study by Ratcliffe et al of recovery from surgery, where data were obtained using wrist-worn accelerometers [12]. A PPI group was surveyed to determine the preferred type of accelerometer device, as well as the acceptability of study contacts and likely familiarity with similar technologies.…”
Section: Participationmentioning
confidence: 99%